Trends in Russia's armed forces an overview of budgets and capabilities - Crane, Keith 1953-; Oliker, Olga 1970-; Nichiporuk, Brian (RAND Corporation, 2019)
The authors provide an overview of the current state of the Russian military in terms of funding and capabilities across the bulk of its forces. They describe how Russian defense budgets have increased over the course of the past 15 years, even as Russian defense spending has now entered a period of decline. They also portray a Russian military in transition, on a path to adapt its general-purpose forces to provide options more suitable to Russia's needs and intentions. They conclude that, based on the location of Russian forces and the systems that the Russian government and military have emphasized for modernization, the Russian government and military have successfully strengthened Russia's military capabilities for a distinct set of future conflict scenarios. It is important to pay close attention to Russia's modernization of its advanced air defenses and ground forces, especially its long-range fires systems -- a process that has improved both its offensive and defensive capabilities. The Russian military has also improved its overall readiness level, which has resulted in an ability to quickly generate significant ground forces and to rapidly project antiair and antisea capabilities around its borders. This gives the country substantial offensive potential against bordering states, especially other former Soviet republics
Keywords: Militär; Militärhaushalt; Russland; Armed Forces / Reorganization; Armed Forces / Appropriations and expenditures; Military policy; Russia (Federation) / Armed Forces / Reorganization; Russia (Federation) / Armed Forces / Appropriations and expenditures / Evaluation; Russia (Federation) / Armed Forces / Operational readiness / Evaluation; Russia (Federation) / Military policy; Military planning / Russia (Federation); Russia (Federation)